A comparison of provisioning systems for beowulf clusters - Trangoni, Mario (2012)
Provisioning Systems were developed to reduce the effort required to install the several components included in the hardware and software stack of High Performance Computing (HPC) clusters. These systems are designed to be turnkey solutions, providing predefined configurations and a myriad of extra tools for management and development. However, as the volume cluster ecosystem grows, so does the number of provisioning systems, and the prospective user has to decide which system is the most adequate. This paper reports a comparative analysis of five provisioning systems for HPC clusters. The analysis was realized as part of the Intel® Cluster Ready program, but the core of the comparison between systems is useful for any organization that wants start using HPC clusters.